PENGARUH INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK SAMSUNG DENGAN BRAND IMAGE SEBAGAI VARIABEL MODERASI (Survei pada Mahasiswa Fakultas Ekonomi UNISRI Surakarta) - Mustika Kusuma Wardani, Sunarso & Retno Susanti (Universitas Slamet Riyadi, 2017)
Samsung company is now a producer of Android phones in the world. To meet theneeds of its customers, the Company Samsung has always product updates by generatingnew products and constantly innovate products and improve product quality to betterdirection. The purpose of this study was to analyze the significance of the influence ofproduct innovation, product quality and brand image of Samsung brand mobile phonepurchasing decisions on the Faculty of Economics, University of Slamet RiyadiSurakarta. Analyzing the moderating effects of brand image on the influence of productinnovation and product quality to the purchasing decision brand mobile phone Samsungat Faculty of Economics, University of Slamet Riyadi Surakarta. This study uses surveymethod, the type of data used quantitative and qualitative data, the data source usedprimary data and secondary data. The population in this study were all students of theFaculty of Economics University of Slamet Riyadi Surakarta. The number of samples inthis study were 100 students, the sampling technique uses accidental sampling. Datacollection methods are used: questionnaires and documentation. Data analysistechnique used to test the validity, reliability test, classic assumption test and multiplelinear regression analysis, t-test, F, coefficient determination and test the absolutedifference. In conclusion: There was a significant effect of product innovation, productquality and brand image of Samsung brand mobile phone purchasing decisions on theFaculty of Economics, University of Slamet Riyadi Surakarta. Brand image does notmoderate the effect of product innovation and product quality to the purchasing decisionbrand mobile phone Samsung at Faculty of Economics, University of Slamet RiyadiSurakarta. This means that the brand image does not amplify the effect of productinnovation on Samsung brand mobile phone purchasing decisions.Keywords: product innovation, product quality, brand image, purchase decisions